Ethnobotanical study on medicinal plants used for jaundice treatment in the Central East of Burkina Faso. - Luc ZONGO; Modeste OUEDRAOGO; M. Sidonie ZONGO; Heiko LANGE; Pascal NADEMBEGA (Journal Africain de Technologie Pharmaceutique et Biopharmacie, 2025)
Abstract: